2019
DOI: 10.1002/ppul.24383
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic paralysis in young children: A literature review

Abstract: Diaphragmatic paralysis (DP) is a rare cause of respiratory distress in young children. In the first years of life, the main cause is phrenic nerve injury after cardiothoracic surgery or obstetrical trauma. DP usually presents as respiratory distress. Asymmetrical thorax elevation, difficulty weaning from mechanical ventilation, pulmonary atelectasis, and repeated pulmonary infections are other suggestive signs or complications. DP is usually suspected on chest X‐ray showing abnormal hemidiaphragm elevation. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
2
8
0
2
Order By: Relevance
“…The present study also found that severe preoperative pulmonary infection was one of the main causes of weaning difficulties in children after cardiac surgery, which is consistent with previous findings ( 12 ). A single-center, 2-year retrospective cohort study of critically ill pediatric patients by ChoiA et al ( 23 ) showed that severe pulmonary infections were responsible for 74.1% of the disease factors influencing the occurrence of weaning difficulties in children, and a large cross-sectional survey of 40 comprehensive ICUs by Louise Rose et al ( 24 ) found that severe pneumonia, acute lung injury, and severe systemic infections with sepsis were responsible for ~64% of the weaning difficulties.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study also found that severe preoperative pulmonary infection was one of the main causes of weaning difficulties in children after cardiac surgery, which is consistent with previous findings ( 12 ). A single-center, 2-year retrospective cohort study of critically ill pediatric patients by ChoiA et al ( 23 ) showed that severe pulmonary infections were responsible for 74.1% of the disease factors influencing the occurrence of weaning difficulties in children, and a large cross-sectional survey of 40 comprehensive ICUs by Louise Rose et al ( 24 ) found that severe pneumonia, acute lung injury, and severe systemic infections with sepsis were responsible for ~64% of the weaning difficulties.…”
Section: Discussionsupporting
confidence: 93%
“…After excluding the weaning failure caused by cardiac surgery, we found out the most critical reasons affecting the weaning failure in pediatric patients with congenital heart diseases, although we were unable to establish direct causality between any of these variables and the weaning procedure. Similar findings were previously identified in patients with diverse heart lesions ( 11 , 12 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Neonatal diaphragmatic paralysis is a rare cause of respiratory distress, traumatic delivery with cervical hyperextension, and/or chest surgery causing phrenic nerve damage (Gerard‐Castaing et al, 2019 ). Birth injury mainly causes unilateral diaphragm injury and is accompanied by ipsilateral brachial plexus injury, resulting in ipsilateral upper limb dyskinesia.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on when or how to intervene in cases of diaphragmatic dysfunction, [15][16][17] Some authors have suggested that this period should be allowed to pass with general supportive treatment, considering that phrenic nerve damage may show spontaneous recovery within one to six weeks. [5,10] On the contrary, Talwar et al [18] recommends a plication procedure as soon as significant diaphragmatic dysfunction is diagnosed.…”
Section: Discussionmentioning
confidence: 99%